2008
DOI: 10.1177/1066896908314700
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Relationship of Human Papillomavirus With Papillary Squamous Cell Carcinoma of the Upper Aerodigestive Tract: A Review

Abstract: The purpose of this review is to evaluate case reports of papillary squamous cell carcinoma (PSCC) of the upper aerodigestive tract (UADT) to assess its relationship with human papillomavirus (HPV). The medical literature was searched for case reports of this condition. A total of 115 cases of PSCC were found that described the condition in sufficient detail. HPV detection was performed in only 22 of the 115 cases of PSCC (19%), and 11 of the 22 cases (50%) are related to this virus. The majority of cases rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…It is most common in the larynx, primarily in the glottis [18], with the same demographics as typical laryngeal keratinizing-type SCC. Papillary SCC also occurs in the oropharynx and nasal cavity [19].…”
Section: Overviewmentioning
confidence: 99%
“…It is most common in the larynx, primarily in the glottis [18], with the same demographics as typical laryngeal keratinizing-type SCC. Papillary SCC also occurs in the oropharynx and nasal cavity [19].…”
Section: Overviewmentioning
confidence: 99%
“…Previous studies have found most of these tumors to be laryngeal or sinonasal, the same sites most frequently involved by squamous papillomas, although the tumors have been described throughout the entire UADT. 5,[11][12][13]20,21 Our higher percentage of oropharyngeal tumors may represent either the changing demographics of UADT SCC, our use of biopsy specimens, or our less stringent histologic criteria (we did not use only those tumors that appeared like ''celery cut across the stalk''). Most patients do not have histories of papillomatosis or other benign lesions, and only uncommonly are such lesions identified with the resection specimens.…”
Section: Detection Of Hpv Infection By In Situ Hybridizationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Microscopically, tumors are composed of papillary fronds lined by a predominately nonkeratinizing SCC in situ that seems similar to SCC in situ of the cervix, replete with full-thickness lack of maturation, cellular and nuclear pleomorphism, and abundant mitotic figures. 6,[10][11][12][13][19][20][21] This is in contrast to keratinizing SCC in situ of the UADT that is typically seen with smokingrelated disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Previous studies have shown that PSCCs are predominantly located on the gingiva and buccal mucosa. It often presents as a solitary lesion with an exophytic or papillary growth pattern.…”
mentioning
confidence: 99%